The clinical instructors’ lived experience in guiding nursing students through their clinical exposure - Solatorio, Mylah B. (Technium Social Sciences Journal, 2026)
This study explored the lived experience of clinical instructors in guiding nursing students through their clinical exposure, with emphasis on their roles, challenges, coping mechanisms, and sustained engagement in clinical teaching. Utilizing a qualitative phenomenological design, the study sought to gain an in-depth understanding of how clinical instructors bridge theory and practice while ensuring patient safety and supporting students’ professional development. Seven clinical instructors were purposively selected through non-probability sampling based on voluntary participation and inclusion criteria, which required at least four years of clinical teaching experience and current employment at the selected university or institution. Participant anonymity was preserved through the use of pseudonyms. Data were collected through in-depth interviews and analyzed using Colaizzi’s method to identify significant statements and generate thematic patterns. Ethical considerations, including informed consent, confidentiality, anonymity, and risk minimization, were strictly upheld throughout the research process. Findings revealed the multifaceted nature of clinical instructors’ experiences, encompassing meaningful teaching moments, complex instructional and emotional challenges, adaptive coping strategies, and strong professional commitment. Four major themes emerged from the analysis: (1) Significant Moments That Shaped Clinical Instructors and Their Students, (2) Challenges of Clinical Instructors in Guiding Nursing Students, (3) Coping Mechanisms of Clinical Instructors From the Challenges in Guiding Nursing Students, and (4) Perceptions of Clinical Instructors and Sustained Engagement in Guiding Nursing Students Through Their Clinical Exposure. These themes highlight the essential role of clinical instructors in fostering students’ clinical competence, emotional resilience, and professional identity while balancing educational responsibilities with patient care demands. The study underscores the need for enhanced institutional support, collaborative academic–service partnerships, and leadership approaches that prioritize instructor well-being and professional development. Such measures are crucial to sustaining effective, resilient, and high-quality clinical nursing education.